Green Electroluminescence of Al/Tb/Al/SiO2 Devices Fabricated by Electron Beam Evaporation (Phys. Status Solidi A 3∕2018). Issue 3 (7th February 2018) - Frieiro, Juan Luis; Blázquez, Oriol; López‐Vidrier, Julian; López‐Conesa, Lluis; Estradé, Sònia; Peiró, Francesca; Ibáñez, Jordi; Hernández, Sergi; Garrido, Blas
Abstract : Nanomultilayers of Al/Tb/Al/SiO2 have been fabricated by e‐beam evaporation, alternatively depositing each layer. Optical characterization of the samples shows a narrow and strong green emission, indicating the optical activation of Tb 3+ ions. The electrical characterization revealed conduction limited by the electrode, although trapped‐assisted mechanisms can also contribute to transport. The electroluminescence analysis revealed also emission from Tb 3+ ions, yielded promising results to include this material in future optoelectronics applications as integrated emitting devices. This is reported by Sergi Hernández and co‐workers in article number1700451 .